The clinical study of 794 patients with an upper urinary tract stone analyzed by infrared spectroscopy - Ishihara, Y (Hinyokika kiyo. Acta urologica Japonica, 1987)
During the 48-year period from January, 1938 to December, 1985, upper urinary tract stones obtained from 794 patients were analyzed by infrared spectroscopy in our Department. Their clinical manifestations were studied, mainly in relation to stone composition. The ratio of males to females was 3.0 to 1. In recent years, the incidence of females tended to increase. In the age distribution, twenties were most frequent followed by thirties together with fourties before 1965, but after 1966, the thirties were most frequent, and fourties and fifties increased. The composition of 794 stones was as follows. The most frequent type was calcium oxalate combined with calcium phosphate (43.1%), followed by calcium oxalate (39.8%) and calcium phosphate (9.6%). Magnesium ammonium phosphate stones were found in 1.6% and uric acid stones in 2.9%. Calcium oxalate stones, uric acid stones and oxalate-containing stones were found more frequently in males than in females. On the other hand, magnesium ammonium phosphate stones, calcium phosphate stones and phosphate-containing stones were found less frequently in males than in females. There was a high occurrence of calcium phosphate stones and uric acid stones in patients older than 60 years old. The occurrence of calcium oxalate stones and uric acid stones increased and that of phosphate-containing stones decreased after 1966. Most of the recurrent stones revealed the same or similar composition as the initial stones